2023
DOI: 10.3390/healthcare11162294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Activity Program on Body Composition, Physical Performance, and Neuromuscular Strategies during Walking in Older Adults with Sarcopenic Obesity: Randomized Controlled Trial

Hamza Ferhi,
Sabri Gaied Chortane,
Sylvain Durand
et al.

Abstract: The potential impact of a specific physical activity program on biomechanical gait parameters and neuromuscular strategies around the ankle joint in older adults with sarcopenic obesity (SO) remains largely unexplored. The objective of this study was to investigate the effectiveness of a 24-week posture, strengthening, and motricity (PSM) program on improving neuromuscular strategies and biomechanical gait parameters in older adults with SO. 40 participants were randomly assigned to either the trained group (T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…The t -test was predefined for power analysis. The estimation was based on predefined controls for type I errors (alpha = 0.05) and Type II errors (beta = 0.60), with a moderate level of estimated effect size (r = 0.30) [ 15 ]. Under these settings, 38 participants were required for the minimum sample size.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The t -test was predefined for power analysis. The estimation was based on predefined controls for type I errors (alpha = 0.05) and Type II errors (beta = 0.60), with a moderate level of estimated effect size (r = 0.30) [ 15 ]. Under these settings, 38 participants were required for the minimum sample size.…”
Section: Methodsmentioning
confidence: 99%
“…Walking is an indicator of autonomy [ 14 ] and plays a key role in disease prevention and weight management in older adults [ 15 ]. It also serves as a crucial diagnostic criterion for conditions like sarcopenia and frailty [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The TMP program is reported using the Template for Intervention Description and Replication (TIDieR) guidelines and is based on the methodology presented in the study of Ferhi et al [30] as demonstrated in Table 1.…”
Section: Intervention Programmentioning
confidence: 99%
“…Tailoring Modifications to the training intensity were assessed after each session using the Rating of Perceived Exertion (RPE) scale, as outlined in the study by Ferhi et al [30].…”
Section: How Muchmentioning
confidence: 99%
See 1 more Smart Citation